Neodymium isotope compositions, rare earth element concentrations and ancillary geochemical data for sediment cores, pore water and bottom seawater from the Atlantic and Pacific Oceans - Sophie Anna Luise Paul; Florian Scholz; Nico Fröhberg; Katja Schmidt (PANGAEA, 2025)
The neodymium (Nd) isotope signature (εNd) has been widely used as a proxy to reconstruct past ocean circulation. Recently it has been increasingly questioned which archives can be reliably used to extract authigenic εNd applied for the reconstruction of past ocean circulation and under which environmental conditions bottom seawater εNd signals are altered and the original water mass signature is overprinted. This dataset publication series contains Nd isotope compositions of pore water, bottom seawater, authigenic and detrital sedimentary phases from the abyssal Atlantic and Pacific Oceans, focusing on the behavior of the Nd isotope composition in oxic deep-sea sediments during early diagenesis. Additionally, it contains dissolved rare earth element and Mn concentrations, dissolved oxygen, TOC, porosity, bulk solid-phase Al, Ca, Fe, and Mn data as well as radiocarbon data as ancillary geochemical data to assist interpretation of the Nd isotope data.